2015
DOI: 10.1080/03670244.2015.1072812
|View full text |Cite
|
Sign up to set email alerts
|

Country food sharing networks, household structure, and implications for understanding food insecurity in Arctic Canada

Abstract: We examine the cultural context of food insecurity among Inuit in Ulukhaktok, Northwest Territories, Canada. An analysis of the social network of country food exchanges among 122 households in the settlement reveals that a household's betweenness centrality-a measure of brokerage-in the country food network is predicted by the age of the household. The households of married couples were better positioned within the sharing network than were the households of single females or single males. Households with an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 41 publications
0
46
0
Order By: Relevance
“…One type of social support network (country food sharing) and its relationship to food security are examined in Ready (2016). Collings et al (2016) use a similar approach, and recent research in Alaska has also focused on sharing networks and cooperative ties (BurnSilver et al, 2016). However, collection of complete network data may be prohibitively costly or too time-consuming for many studies because of sampling requirements.…”
Section: Discussion: Food Security In a Mixed Economymentioning
confidence: 99%
“…One type of social support network (country food sharing) and its relationship to food security are examined in Ready (2016). Collings et al (2016) use a similar approach, and recent research in Alaska has also focused on sharing networks and cooperative ties (BurnSilver et al, 2016). However, collection of complete network data may be prohibitively costly or too time-consuming for many studies because of sampling requirements.…”
Section: Discussion: Food Security In a Mixed Economymentioning
confidence: 99%
“…The pattern of declining local food consumption, increasing consumption of nutrient-poor nontraditional foods, substantial decreases in health, changing food-sharing networks, and increases in diet-related disease documented in Pacific Islands are similar to that observed elsewhere, particularly among indigenous populations (e.g., Gracey, 2000, Lowitt, 2014, Scelza et al 2014, Ghosh-Jerath et al 2015, Laberge Gaudin et al 2015, Mertens et al 2015, Collings et al 2016). …”
Section: Introductionmentioning
confidence: 58%
“…However, we found that landings in high harvest years tend to be spread evenly throughout July, with short gaps (i.e., 2-3 days), suggesting that harvesters are limited in their ability to make up for lost days by increasing effort on other days. Stresses affecting food security, as well as societal changes to language and land-based skills, are growing concerns across the Arctic and have been examined in numerous studies (Condon et al 1995;Harder and Wenzel 2012;Collings et al 2016). The annual beluga harvest provides a nutritionally superior alternative to store-bought products (Hoover et al 2016) and provides an opportunity to pass on traditional hunting and land-based skills to younger generations (Pearce et al 2011).…”
Section: Socio-economic Impact On the Huntmentioning
confidence: 99%